FOLKLORE OF TURKIС PEOPLE (ON THE EXAMPLE OF FOLK : FOLKLORE OF TURKIС PEOPLE (ON THE EXAMPLE OF FOLK TALE GENRE) - Kholmurodova, Olima (Журнал иностранных языков и лингвистики, 2021)
FOLKLORE OF TURKIС PEOPLE (ON THE EXAMPLE OF FOLK TALE GENRE)